Pemanfaatan Filtrasi Air Sumur untuk Mengurangi Kekeruhan Menggunakan Penyaringan Air Sederhana di Kelurahan Pahang - Rizqi Dwi Nugraha; Jihan Nabila; Fatya Sheila Husna; Devi khairani; Yolanda Afifa; Ridwan Yusuf Lubis (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Water is the most important substance in human life, so its availability is very important for life. Its utilization is also very much needed by humans, because this water is a source of life for every human being and also for household purposes. But most people still use underground dug well water for use in daily life, due to the difficulty of pumping water in the area. This research was conducted in Pahang Village, Datuk Bandar Subdistrict, Tanjung Balai City in July-August 2022. The purpose of this research is to make a simple water filter, to be able to help residents, and also conduct water education, with the hope that residents can understand and be aware of the importance of clean water.